2013
DOI: 10.1585/pfr.8.3404055
|View full text |Cite
|
Sign up to set email alerts
|

Ultraintense Lasers as a Promising Research Tool for Fusion Material Testing: Production of Ions, X-Rays and Neutrons

Abstract: Laser fusion environments are characterized by prompt bursts of high energy neutrons, ions and X-rays which are absorbed by different components of the fusion reaction chamber. In particular, plasma facing components are subjected to extreme conditions and prior to their use in the reactors they must be validated under stringent irradiation tests. However, the particular characteristics of the fusion products, i.e. very short pulses, very high fluences and broad particle energy spectra are difficult to reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Alvarez et al 30 demonstrated that the experimental energy distribution of the proton beam generated from laser acceleration is very similar to the proton burst produced in an ICF experiment using a shock ignition target of 48 MJ, in particular for the energy range of 2–6 MeV. We therefore ensured that our proton spectrum was containing these proton energies.…”
Section: Resultsmentioning
confidence: 74%
“…Alvarez et al 30 demonstrated that the experimental energy distribution of the proton beam generated from laser acceleration is very similar to the proton burst produced in an ICF experiment using a shock ignition target of 48 MJ, in particular for the energy range of 2–6 MeV. We therefore ensured that our proton spectrum was containing these proton energies.…”
Section: Resultsmentioning
confidence: 74%